Biomarkers for early detection of non-alcoholic steatohepatitis: Implications for drug development and clinical trials - (:unkn) unknown (My University, 2013)
The term non-alcoholic fatty liver disease (NAFLD) comprises at least four pathological entities (definite nonalcoholic steatohepatitis [NASH], borderline "zone 3" pattern, borderline "zone 1" pattern, not steatohepatitis with steatosis) with distinct patterns of lipid storage, fibrosis, and hepatocyte injury. Recent pathophysiological advances hold promise to provide much needed surrogate non-invasive biomarkers to detect steatohepatitis, fibrosis, and monitor NASH progression (or resolution, in the setting of clinical trials) without the cumbersome use of liver biopsy. Herein, we reviewed the current status of multimodal biomarker candidates derived from biochemical and genetic studies of NASH, as well as potential markers derived from imaging studies. A literature search was conducted in March 2013 on PubMed, Ovid Embase, Ovid Medline and Scopus using the following search terms: steatosis, non-alcoholic steatohepatitis, biomarker, genetics, imaging, clinical trials. Rather than to biopsy, the identification of steatohepatitis and fibrosis may originate primarily from prespecified multimodal biomarker data, including positive findings on serum or genetic biomarkers, and imaging tests like MR elastography or Fibroscan. In the setting of clinical trials, it seems recommendable to widen and expand the therapeutic vision beyond insulin resistance and focus on trials in very early NASH stages. The paradigm shift towards an earlier noninvasive characterization and diagnosis of NASH and fibrosis will be crucial to redefine and establish successful interventional trials. © 2013 Bentham Science Publishers.
Keywords: Biomarkers; Biopsy; Clinical trials; Imaging; Nonalcoholic fatty liver disease; Treatment